2012
DOI: 10.1073/pnas.1201313109
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid addition to Vibrio cholerae LPS establishes a link between surface remodeling in Gram-positive and Gram-negative bacteria

Abstract: Historically, the O1 El Tor and classical biotypes of Vibrio cholerae have been differentiated by their resistance to the antimicrobial peptide polymyxin B. However, the molecular mechanisms associated with this phenotypic distinction have remained a mystery for 50 y. Both Gram-negative and Gram-positive bacteria modify their cell wall components with amine-containing substituents to reduce the net negative charge of the bacterial surface, thereby promoting cationic antimicrobial peptide resistance. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
186
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(192 citation statements)
references
References 29 publications
6
186
0
Order By: Relevance
“…In Gram-negative bacteria, lipid A in the outer membrane is the substrate for various positively charged modifications. Biosynthesis pathways for these modifications are not shown (For details see [116-118]). In certain species of both Gram-positive and Gram-negative bacteria, aminoacyl-phosphatidylglycerol synthases (aaPGSs) transfer aa from aa-tRNA (pre-formed by cytosolic aa-tRNA synthetases, aaRS) to phosphatidylglycerol (PG) in the membrane.…”
Section: Cationic Antimicrobial Peptides (Camps) and Bacterial Resistmentioning
confidence: 99%
“…In Gram-negative bacteria, lipid A in the outer membrane is the substrate for various positively charged modifications. Biosynthesis pathways for these modifications are not shown (For details see [116-118]). In certain species of both Gram-positive and Gram-negative bacteria, aminoacyl-phosphatidylglycerol synthases (aaPGSs) transfer aa from aa-tRNA (pre-formed by cytosolic aa-tRNA synthetases, aaRS) to phosphatidylglycerol (PG) in the membrane.…”
Section: Cationic Antimicrobial Peptides (Camps) and Bacterial Resistmentioning
confidence: 99%
“…S1), which is denoted as VC-A. Hankins et al (35) reported the chemical modifications of a glycine or diglycine residue to the C3 0 position secondary acyl chain, which are denoted as VC-B (glycine) and VC-C (diglycine), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrio cholerae is the causative agent of cholera, which is usually transmitted by unclean water and often causes severe diarrhea in humans and animals (35). V. cholerae lipid A consists of the standard headgroup and six acyl chains.…”
Section: Methodsmentioning
confidence: 99%
“…Both BPI and polymyxin B are thought to interact with the lipid A moiety of lipopolysaccharide (LPS). In fact, lipid acylation catalyzed by MsbA/LpxN (VC0212), the genes for which encode a lipid A secondary hydroxyacyltransferase, and glycine and diglycine modification catalyzed by AlmG (VC1577), AlmF (VC1578), and AlmE (VC1579) were found to be critical for V. cholerae polymyxin B resistance (5,6). It is proposed that a decrease in cell surface negative charge and membrane fluidity resulting from the glycine modification could impact antimicrobial peptide resistance.…”
mentioning
confidence: 99%